PSA im Extrembereich – Ausdruck einer infausten Prognose? Eine Übersicht über Verlauf und Therapie des Prostatakarzinoms mit PSA-Werten (prostataspezifisches Antigen) im drei- bis vierstelligen Bereich - Dirscherl, Christian; Ebert, Thomas; Schmitz-Dräger, Bernd J.; Goebell, Peter (Die Urologie, 2025)
Background: Extremely high baseline prostate-specific antigen (bPSA) values in the range of 100 to ≥ 1000 ng/ml prior to the start of systemic therapy pose a challenge, as they can lead to the impression of a very unfavorable prognosis. Objective: We investigated factors influencing 5‑year overall survival (5-yOS) and the treatment modalities of patients with bPSA levels ≥ 100 ng/ml using retrospective data. Materials and methods: We defined items from a limited initial collective, which we then used for a query in the UroCloud database. A total of 695 patients were included. Results and conclusion: For the entire collective, the 5‑yOS was 68.5% ± 2.7%. The bPSA value had a significant (p < 0.001) influence on 5‑yOS in the following groups: 100–149 ng/ml, 150–249 ng/ml, 250–649 ng/ml, and ≥ 650 ng/ml (5-yOS: 77.0% ± 4.9% vs. 76.9% ± 4.5% vs. 61.4% ± 6.0 vs. 57.4% ± 6.1%, respectively). Age ≤ 70 years compared to > 70 years at first diagnosis resulted in a significant difference regarding 5‑yOS (74.8% ± 3.5% vs. 60.1% ± 4.4, respectively). A PSA response of > 90%, which was achieved in 79.0% of cases, had a significant influence on 5‑yOS compared to a response of ≤ 90% (73.5% ± 2.9% vs. 48.6% ± 6.7%, respectively). There was also a significant 5‑yOS advantage if a first PSA nadir of ≤ 0.20 ng/ml was achieved (in 22.2%) compared to a first PSA nadir of > 0.20 ng/ml (89.8% ± 3.3% vs. 60.4% ± 3.5%, respectively). In 49.4% (n = 343) of cases, androgen deprivation therapy (ADT) monotherapy was started as first-line systemic therapy. Between 1999 and 2023, we saw an increase in escalated and initial combination therapies. The analysis shows that an extreme bPSA value is not in itself an expression of an unfavorable prognosis.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Database; Prognosis; Prostate neoplasms; Prostate-specific antigen; Real world